Hand Hygiene Audit and Practices among Resident Doctors and Nursing Staff Working at Pediatric and Neonatal Intensive Care Unit: An Observational Study: Hand Hygiene Compliance, Knowledge and Practices in ICU (GAIMS Journal of Medical Sciences, 2024)
Background: To lower the frequency of healthcare-associated infections (HCAIs), it is critical to analyze existing hand hygiene (HH) practices among healthcare workers (HCWs), identify gaps, and implement corrective actions. We planned to evaluate HCWs' hand hygiene routines with this objective in mind.Methods: The study focused on postgraduate resident doctors and nursing staff's hand hygiene habits over three months at a teaching hospital providing tertiary care. Direct observation and survey-based cross-sectional methods were utilized, with an observation tool and questionnaire employed for data collection; the observation period for hand hygiene compliance lasted six to eight weeks, with observations made at random intervals during morning, evening, and night shifts in the PICU and NICU.Results: The study observed a statistically significant compliance rate for hand hygiene among nursing staff and resident doctors, with 160 out of 172 observations demonstrating hand hygiene practices. Adequate hand hygiene performance was observed in 69.4% of cases, which was also statistically significant. Alcohol-based hand rub was more frequently used than soap. The analysis of knowledge, attitude, and practices included 20 resident doctors and 24 nursing staff in the PICU and NICU. The results showed that 97% of participants had received hand hygiene education in the past year, and nearly 100% used alcohol hand rub consistently. Most respondents, 90% of resident doctors and 83.4% of nursing staff recognized the significant impact of healthcare-associated infections on patient outcomes. Additionally, 85% of nursing staff and 95% of resident doctors agreed that maintaining good hand cleanliness is essential for reducing healthcare-associated illnesses.Conclusion: The findings of this study revealed that the participants had an excellent knowledge of hand hygiene. To emphasize the value of hand washing for both patients and healthcare workers, we advise providing the appropriate tools and holding instructional workshops. Such measures would significantly improve attitudes towards hand hygiene, reducing preventable infections, shorter hospital stays, and cost savings in healthcare.